Dynamic performance assessment of a solar-assisted desiccant-based air handling unit in two Italian cities. (1st April 2016) - Angrisani, G.; Roselli, C.; Sasso, M.; Tariello, F.
Highlights: A hybrid desiccant-based air handling unit is coupled with solar collectors. TRNSYS models are developed to simulate different air-conditioning systems. Dynamic simulations are performed for two different cities with different climates. A thermo-economic analysis is carried out considering different collectors type. Thermo-economic performance increases with the use of solar thermal energy surplus. Abstract: Desiccant-based air handling units can provide significant operational advantages and can use solar energy as the main heat source. Hereinafter a plant equipped with a silica-gel desiccant wheel is analyzed for two Italian locations (Benevento and Milano). A parametric study involving collectors types, surfaces, tilt angles and installation site has been performed. The proposed system has been compared with a conventional HVAC unit, through dynamic simulations. In terms of energy and environmental analysis, solar desiccant systems should always be preferred to conventional ones, even when the solar thermal energy surplus is fully dissipated. A maximum primary energy saving of about 10% and 20% with flat plat and evacuated tube collectors, respectively, occurs in both locations. The savings increase up to about 58% and 72% in Benevento and 43% and 58% in Milano, when the solar heat excess is completely used for further energy demands. One observes that systems with evacuated tube collectors are preferable where the available space for the solar field is small, instead with larger surfaces flat plate collectors are advantaged. In terms of economic analysis, the shortest payback periods are 6 and 8 years for Benevento and Milano, respectively.